On noise figures in transistor audio amplifiers - Bhagiratharao, E. (Defence Science Journal, 2014)
The noise figures of two general purpose transistors of Philips and Hitachi (Japanese) make have been determined under identical experimental conditions with a view to see whether they differ in their noise properties. The variation of noise figure of Philips as well as Hitachi transistors with (i) frequency (ii) collector voltage (iii) collector current (iv) emitter current (v) input impedance have been investigated. It was concluded that Philips and Hitachi transistors do not differ much in their noise properties, when operated under identical conditions. For both the transistors the noise figure increase with collector voltage, collector current and emitter current. Increasing input impedance of either of the transistors increases the noise figure when the input impedance exceeds two thousand ohms. For both transistors the noise figure decrease with frequency, then remains constant over a small frequency band and finally increases slowly with frequency.